(untitled) (Research, Society and Development, 2019)
Economic sector is one of public welfare benchmarks as outlined in the opening of the 4th paragraph of the 1945 Constitution, namely the welfare of the nation’s life. In the current economic development, it has triggered the importance of investment for Indonesia to be able to compete in the realm of global market competition. But the dependence on foreign investment will be a boomerang for Indonesia. Thus, this study is aimed to find out the investment law regulate by Government in Indonesia. Afterward, normative approach relating to foreign investment in Indonesia will be described as method in this study. Based on the study, it was concluded that with the existence of Law Number 25/2007 concerning investment and various implementing regulations, it was one form of government action concerned with the development of the investment sector. Therefore, the regulation can provide legal protection for both Indonesian citizens and foreign investors.